Transport and Transformation of Selenium and Other Constituents of Flue‐Gas Desulfurization Wastewater in Water‐Saturated Soil Materials. Issue 2 (1st March 2017) - Galkaduwa, Madhubhashini B.; Hettiarachchi, Ganga M.; Kluitenberg, Gerard J.; Hutchinson, Stacy L.; Davis, Lawrence; Erickson, Larry E.
Abstract : Constructed wetland treatment systems are used to remove selenium (Se) from flue‐gas desulfurization (FGD) wastewater (WW). However, direct confirmation of the mechanism responsible for FGD WW Se retention in soil is lacking. A laboratory‐based soil column study was performed to develop an evidence‐based mechanism of Se retention and to study the behavior and the retention capacity of FGD WW constituents in water‐saturated soil. A deoxygenated 1:1 mixture of FGD WW and raw water was delivered to the columns bottom‐up at a flux of 1.68 cm d −1 for 100 d. Some of the columns were flushed with the raw water at the same rate for an additional 100 d. Column effluent was analyzed for constituents of concern. Results showed a complete retention of FGD WW Se in the soil materials. Boron and fluorine were partially retained; however, sulfur, sodium, and chlorine retention was poor, agreeing with field observations. The FGD WW Se was retained in soil near the inlet end of the columns, indicating its limited mobility under reduced conditions. Sequential extraction procedure revealed that retained Se was mainly sequestered as stable/residual forms. Bulk‐ and micro‐X‐ray absorption near‐edge structure spectroscopy confirmed that Se was mainly retained as reduced/stable species [Se(IV), organic Se, and Se(0)]. This study provides direct evidence for FGD WW Se retention in water‐saturated soil via the transformation of oxidized Se into reduced/stable forms. Core Ideas: The mechanism of FGD wastewater Se retention in water‐saturated soil was studied. Sequential fractionation of Se, micro‐XRF, and micro‐ and bulk‐XANES were used. Behavior of FGD wastewater constituents in saturated soil was comparable to field‐scale observations. FGD wastewater Se exhibited strong retention in reduced soil. Reduced/stable species of Se governed the retention mechanism.